The Association of CYP2D6 Genotype and Postoperative Nausea and Vomiting in Orthopedic Trauma Patients. (October 2013) - Wesmiller, Susan W.; Henker, Richard A.; Sereika, Susan M.; Donovan, Heidi S.; Meng, Li; Gruen, Gary S.; Tarkin, Ivan S.; Conley, Yvette P.
The CYP2D6 gene encodes for an enzyme that is involved in the metabolism of more than 25% of all medications, including many opioids and antiemetics. It may contribute to the risk of postoperative nausea and vomiting (PONV), a common surgical complication. However, little research has been conducted in this area. The purpose of this study was to explore the association of CYP2D6 genotypes with PONV in adult surgical trauma patients. Data from 112 patients (28% female) with single extremity fractures, aged 18–70 years, were analyzed. PONV was defined as present if patients reported nausea, were observed vomiting, or received medication for PONV. Saliva samples collected for DNA extraction and Taqman ® allele discrimination and quantitative real time polymerase chain reaction (qRT-PCR) were used to collect genotype data that were then used to assign CYP2D6 phenotype classification. The incidence of PONV was 38% in the postanesthesia care unit and increased to 50% when assessed at 48 hr. CYP2D6 classification results were 7 (6%) poor metabolizers, 34 (30%) intermediate metabolizers, and 71 (63%) extensive metabolizers. No ultrarapid metabolizers were identified. Patients who were classified as poor metabolizers had less PONV and higher pain scores. Gender and history of PONV, but not smoking, were also significant risk factors. Findings suggest variability in CYP2D6 impacts susceptibility to PONV.